Resistance to cyclin-dependent kinase (CDK) 4/6 inhibitors confers cross-resistance to other CDK inhibitors but not to chemotherapeutic agents in breast cancer cells - Ogata, Ryohei (Breast Cancer, 2020)
BACKGROUND: Combined endocrine therapy with a cyclin-dependent kinase (CDK) 4/6 inhibitor has been indicated to improve not only progression-free survival, but also overall survival in patients with hormone receptor (HR)-positive, HER2-negative advanced breast cancer. However, resistance to this combination therapy inevitably develops. How to manage this resistant breast cancer is one of the most important clinical issues. To investigate the mechanisms of action responsible for resistance, we developed breast cancer cells resistant to CDK4/6 inhibitors, and analyzed their biological characteristics and sensitivity to different anticancer agents. METHODS: HR-positive, HER2-negative MCF-7 and KPL-1 breast cancer cells were cultivated in palbociclib (PAL) or abemaciclib (ABE)-added culture medium for over 5 months, and we successfully developed PAL- or ABE-resistant cells. The effects of PAL or ABE on the cell growth, basal RB expression, RB phosphorylation, cell cycle and cell senescence were compared between resistant and parental cells. Effects of the other CDK4/6 inhibitor, different chemotherapeutic agents and estrogen on the cell growth were also examined. The expression levels of cyclin D1, CDK2, CDK4, CDK6, cyclin E1 and estrogen receptor (ER)-ɑ were measured using RT-PCR. RESULTS: Long-term exposure to up to 200 nM PAL or ABE resulted in the development of PAL- or ABE-resistant MCF-7 or KPL-1 breast cancer cells. Basal expression levels of RB in both resistant cells were down-regulated. Inhibitory effects of either PAL or ABE on RB phosphorylation were reduced in both resistant cells. Accordingly, G1-S cell cycle retardation and cell senescence induced by either inhibitor were also attenuated in both resistant cells. Both resistant cells were cross-resistant to the other CDK4/6 inhibitor but almost as equally sensitive to different chemotherapeutic agents (5-fluorouracil, gemcitabine, paclitaxel, docetaxel, doxorubicin and eribulin) as the parental cells. The mRNA expression level of CDK6 significantly increased in the resistant MCF-7 cells and that of Rb1 significantly decreased in the resistant KPL-1 cells. Although both resistant cells were less sensitive to estrogen than the parental cells, the expression levels of ER-ɑ did not significantly change in either. CONCLUSIONS: Our study suggests that acquired resistance to PAL or ABE confers cross-resistance to the other CDK4/6 inhibitor but not to chemotherapeutic agents in HR-positive, HER2-negative breast cancer cells. Down-regulation of basal RB expression and normalized RB phosphorylation reduced by CDK4/6 inhibitors may be responsible for the attenuated anti-cell growth effects of the inhibitors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12282-020-01150-8) contains supplementary material, which is available to authorized users.